EVALUACIÓN DEL DESARROLLO DE LA REFRACTARIEDAD PLAQUETARIA EN PACIENTES CON NEOPLASIAS DE ORIGEN HEMATOLÓGICO, TRANSFUNDIDOS CON CONCENTRADOS DE PLAQUETAS OBTENIDOS POR EL MÉTODO CB~BC EN PRESENCIA Y AUSENCIA DE FILTROS DESLEUCOCITARIOS (2013)
Development of permanent platelet refractoriness is a majar problem in multitransfused patients with hematologicmalignancies. Tbe systematic leukocyte reduction of blood components transfused, guided to reduce it, mayincrease the cost of the transfusional therapy, specially by the application of leukocyte adsorption filters. Westudied the development of platelet refractoriness in 83 patients with hematologic malignancies, that had beentransfunded with platelet concentrates derived from Buffy Coat, with or without the use of leukocyte depletionfilters. No significant difference (p = 0.378) was found between both groups; for the refractoriness development.Additionally, the cost of the therapy increased about four times, (p<O.OOO 1) when the filters applied.